Molecular characterization of the hexose transporter (PfHT1) of Plasmodium falciparum in Xenopus laevis oocytes - Louw, Abraham Izak (University of Pretoria, 2013)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2005.